2022
DOI: 10.3386/w30806
|View full text |Cite
|
Sign up to set email alerts
|

Negotiations of Oil and Gas Auxiliary Lease Clauses: Evidence from Pennsylvania’s Marcellus Shale

Abstract: Oil and gas lease negotiations provide mineral owners the opportunity to negotiate for both compensation and auxiliary clauses that may protect their health and properties. We use optical character recognition to assemble a novel dataset of compensation and specific clauses in nearly 60,000 leases signed in the Marcellus Shale Play of Pennsylvania. We leverage the dataset to produce three main findings. First, contrary to the standard utility maximization model, we find a positive relationship between compensa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Using natural gas leasing data, Timmins and Vissing (2022) found that Hispanic landowners had fewer environmental protections in their natural gas royalty contracts. Similarly, Harleman et al (2022) found that high-income landowners had the resources to negotiate more favorable oil and gas agreements.…”
Section: Understanding Energy Paymentsmentioning
confidence: 98%
See 2 more Smart Citations
“…Using natural gas leasing data, Timmins and Vissing (2022) found that Hispanic landowners had fewer environmental protections in their natural gas royalty contracts. Similarly, Harleman et al (2022) found that high-income landowners had the resources to negotiate more favorable oil and gas agreements.…”
Section: Understanding Energy Paymentsmentioning
confidence: 98%
“…41 The effect, however, was small; a 10-percent increase in farm wealth was associated with about a one-tenth of 1-percent increase in the likelihood of receiving payments relative to the average of 3.5 percent. Nonetheless, the finding suggests that wealthier operators may have more resources to negotiate energy leases (Harleman et al, 2022). The finding also implies that less wealthy farms are not disproportionately entering into energy leases to diversify income, while wealthier farms may be using energy income as one of many sources of diversification.…”
mentioning
confidence: 94%
See 1 more Smart Citation